(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
The article analyzes the results of determining the level of salinization of irrigated agricultural land and creating cartograms in the Boz district of the Andijan region, which is part of the territory of Central Fergana. When determining the level of salinity, taking into account the location of the object of study of the area, the chemistry of salinity, the secondary level of soil salinity are determined and recommendations are given on the rate, duration and number of salt flushes